Medieval Islamic philosophical writings - Khalidi, Muhammad Ali (Professor of philosophy) (Cambridge texts in the history of philosophy., 2005)
This volume presents a selection of texts by the most celebrated philosophers of the classical period of Islam, including Farabi, Ghazali (Avicenna) and Ibn Rushd (Averroes). An introduction situates the text in their philosophical and historical contexts, and the volume also includes helpful notes on further reading.